Laminated cores, noise filters, magnetic cores

By controlling the interlayer distance ratio and using high glass transition temperature resin with low viscosity, the laminated core maintains shape and achieves high magnetic permeability, enhancing noise suppression and efficiency in noise filters and magnetic cores.

JP7608498B2Active Publication Date: 2025-01-06RIKEN CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023038113
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2025-01-06
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

Laminated cores made of soft magnetic metal ribbons experience reduced magnetic permeability due to resin distortion during the curing process, which is caused by variations in the thickness of the impregnated resin between layers.

Method used

The laminated core is designed with a specific ratio of the total interlayer distance to the average interlayer distance (R = S4/S) of 10.0% or less, using a resin with a glass transition temperature of 85°C or higher, and impregnating the soft magnetic metal ribbons with a low viscosity resin to maintain shape and prevent distortion.

Benefits of technology

The solution results in a laminated core with high magnetic permeability, enabling effective noise suppression in noise filters and efficient operation of magnetic cores, even in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608498000002
    Figure 0007608498000002
  • Figure 0007608498000003
    Figure 0007608498000003
  • Figure 0007608498000004
    Figure 0007608498000004
Patent Text Reader

Abstract

To provide a laminated core with high permeability, a noise filter with high noise suppression effect, and a magnetic core with high efficiency.SOLUTION: A laminated core 1 consists of a magnetic material composed of laminated soft magnetic metal thin strips 2, and has a resin 3 between layers of soft magnetic metal thin strips, When the total interlayer distance d of the soft magnetic metal thin strips is S, the average of the interlayer distances d of the soft magnetic metal thin strips is dave, and the total interlayer distance between the layers of the soft magnetic metal thin strips where the interlayer distance is four times greater than the average dave is S4, the ratio of the total S4 to the total S, R4=S4 / S, is equal to or less than 10.0%. The noise filter and the magnetic core are based on the laminated cores.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated core, and a noise filter and a magnetic core each using the laminated core. [Background technology]

[0002] Laminated cores made by laminating soft magnetic metal ribbons are used as noise filters and magnetic cores for transformers, motors, etc. Generally, laminated cores made by simply laminating soft magnetic metal ribbons are weak in strength and cannot maintain their shape, so resin is filled between the layers of the soft magnetic metal ribbons as an adhesive, and the strength is increased by solidifying and molding.

[0003] In Patent Document 1, a wound core of a nanocrystalline alloy is impregnated with resin in order to form a gap in the magnetic core for a choke coil (hereinafter, such a resin is also referred to as "impregnated resin"). An epoxy resin is used as the impregnated resin.

[0004] In addition, in Patent Document 2, a wound core of nanocrystalline alloy foil is cut into separate shapes for use in noise filters, and is then impregnated with resin and solidified. It is explained that the impedance is less likely to decrease even when the core is cut by specifying the thickness of the resin layer relative to the thickness of the nanocrystalline alloy foil. Epoxy resin is also used as the impregnating resin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 9-027413 [Patent Document 2] JP 2021-163772 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, it has been found that in the laminated core described above, the magnetic permeability may be lower than expected.

[0007] SUMMARY OF THE PRESENT DISCLOSURE In view of the above, an object of the present invention is to provide a laminated core having high magnetic permeability, a noise filter having a high noise suppression effect, and a highly efficient magnetic core. [Means for solving the problem]

[0008] The inventors of the present invention have conducted extensive research to solve the above problems, and have found that the magnetic permeability of a laminated core is reduced by distortion during hardening treatment after impregnation caused by variations in the thickness of the impregnating resin between layers. In a laminated core in which resin is impregnated between layers of soft magnetic metal ribbons and then solidified, the average d of the interlayer distances d of the soft magnetic metal ribbons to the total S of the interlayer distances d of the soft magnetic metal ribbons is ave The inventors have found that the above-mentioned problem can be advantageously solved by setting the ratio R4 of the total interlayer distance S4 of the soft magnetic metal ribbons, which is four or more times larger than the total interlayer distance S4, to 10.0% or less, and have completed the present invention.

[0009] The gist and configuration of the present invention are as follows. (1) A laminated core made of a magnetic material formed by laminating soft magnetic metal ribbons, A resin is disposed between the layers of the soft magnetic metal ribbon, The total interlayer distance d of the soft magnetic metal ribbons is S, and the average interlayer distance d of the soft magnetic metal ribbons is d ave and the interlayer distance between the layers of the soft magnetic metal ribbon is the average d ave When the total interlayer distance between layers that is four times or more is S4, A laminated core, characterized in that a ratio R4=S4 / S of the sum S4 to the sum S is 10.0% or less. Here, the "interlayer distance d of the soft magnetic metal ribbon" refers to the distance between each layer present on three radial lines spaced at 120° intervals in a side view of the laminated core, as shown typically in FIG. 3. Also, the "interlayer distance d of the soft magnetic metal ribbon" is measured for each interlayer present in a radial region that is 90% of the entire radial length, consisting of a radial region of the laminated core that is 45% of the entire radial length on the radial outside and a radial region of the laminated core that is 45% of the entire radial length on the radial inside, as shown typically in FIG. 2. Note that the interlayers located at the ends of the radial region that is 90% of the entire radial length are not included in the measurement. Therefore, the "total interlayer distances S" and the "average interlayer distances d d" are calculated based on the "total interlayer distances S" and "average interlayer distances d d" of ... ave " and "Average d ave The total interlayer distance S4 between the layers, which is four times or more of the total radial distance S4, is calculated from the interlayer distance d of the soft magnetic metal ribbon between all layers present in a radial region that is 90% of the total radial length of the three radial lines. The interlayer distance d of the soft magnetic metal ribbon can be measured using an optical microscope.

[0010] (2) The laminated core according to (1), wherein the glass transition temperature of the resin between the layers of the soft magnetic metal ribbon is 85° C. or higher.

[0011] (3) The laminated core according to (1), wherein the glass transition temperature of the resin between the layers of the soft magnetic metal ribbon is 125° C. or higher.

[0012] (4) The laminated core according to any one of (1) to (3), wherein the ratio R4=S4 / S is 10.0% or less.

[0013] (5) The laminated core according to any one of (1) to (4), wherein the soft magnetic metal ribbons are made of a nanocrystalline alloy.

[0014] (6) The laminated core according to any one of (1) to (4), wherein the soft magnetic metal ribbons are made of an amorphous alloy.

[0015] (7) The laminated core according to any one of (1) to (6), which has an impedance relative permeability μrz of 10,000 or more at 100 kHz.

[0016] (8) The laminated core according to any one of (1) to (7) above, which is formed by combining a plurality of annular laminated magnetic pieces having discontinuous portions that are interrupted in the circumferential direction.

[0017] (9) A noise filter using the laminated core according to any one of (1) to (8) above. (10) A magnetic core for a transformer or a motor, which uses the laminated core according to any one of (1) to (8) above. Effect of the Invention

[0018] According to the present invention, it is possible to provide a laminated core having high magnetic permeability, a noise filter having a high noise suppression effect, and a highly efficient magnetic core. [Brief description of the drawings]

[0019] [Figure 1] FIG. 2 is a side view of a laminated core according to one embodiment of the present invention. [Diagram 2] FIG. 13 is a schematic diagram for explaining the measurement range of the total interlayer distance S and the average interlayer distance dave. [Diagram 3] FIG. 2 is a schematic diagram for explaining a method for measuring an interlayer distance d. [Figure 4] FIG. 2 is a diagram showing one of the observation images obtained by measuring the metal ribbon interlayer distance in Example 1. [Diagram 5] 4 is a histogram of the metal ribbon interlayer distance in Example 1. [Figure 6] FIG. 13 is a diagram showing one of the observation images obtained by measuring the interlayer distance of the metal ribbon in Comparative Example 1. [Figure 7] 1 is a histogram of the metal ribbon interlayer distance in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings.

[0021] <Laminated core> Fig. 1 is a side view of a laminated core according to one embodiment of the present invention. As shown in Fig. 1, this laminated core 1 is made of a magnetic body formed by laminating soft magnetic metal ribbons 2. The laminated core 1 has a cylindrical shape. Resin (impregnated resin in an impregnated state) 3 is present between the layers of the soft magnetic metal ribbons 2. Fig. 1 is a schematic diagram, and the laminated core 1 is an annular magnetic body that is laminated in the radial direction by winding the soft magnetic metal ribbons 2 into a roll and has resin 3 between the layers. Although not particularly limited, the outer diameter of the laminated core 1 can be 15 to 250 mm, the inner diameter can be 6 to 155 mm, and the height (the axial height of the cylindrical shape) can be 3 to 100 mm.

[0022] <<Soft magnetic metal ribbon>> The soft magnetic metal ribbon 2 preferably has a small coercive force and a large magnetic permeability. As the soft magnetic material of the soft magnetic metal ribbon 2, for example, soft magnetic metals such as Fe-Ni alloys (permalloys) and Fe-Si alloys (silicon steel), amorphous alloys such as Co-based amorphous alloys and Fe-based amorphous alloys, and Fe-based nanocrystalline alloys can be used. Specifically, the soft magnetic metal ribbon 2 is preferably made of a nanocrystalline alloy or an amorphous alloy.

[0023] When an amorphous alloy or an Fe-based nanocrystalline alloy is used as the soft magnetic metal ribbon 2, for example, the general formula: (Fe 1-a M a ) 100-x-y-z-b-c-d A x M' y M” z X b S c B d(atomic %) (wherein M is at least one element selected from Co and Ni, A is at least one element selected from Cu and Au, M' is at least one element selected from Ti, V, Zr, Nb, Mo, Hf, Ta, and W, M" is at least one element selected from Cr, Mn, Sn, Zn, Ag, In, platinum group metal elements, Mg, N, and S, X is at least one element selected from C, Ge, Ga, Al, and P, and a, x, y, z, b, c, and d satisfy 0≦a≦0.1, 0.1≦x≦3, 1≦y≦10, 0≦z≦10, 0≦b≦10, 11≦c≦17, 3≦d≦10, and 65≦100-xyzbcd≦85, respectively) can be used.

[0024] The composition of the Fe-based nanocrystalline alloy is not particularly limited, but is preferably, in atomic percent, Cu: 0.5-2.0%, Nb: 1.0-5.0%, Si: 11.0-15.0%, B: 5.0-10.0%, with the remainder being substantially Fe, but is not limited thereto as long as the properties of the present disclosure are satisfied.

[0025] When an amorphous alloy or an Fe-based nanocrystalline alloy is used as the soft magnetic metal ribbon 2, the thickness of the soft magnetic metal ribbon 2 is not particularly limited, but can be, for example, 10 to 30 μm. By making the thickness of the soft magnetic metal ribbon 2 30 μm or less, the cooling speed can be sufficiently increased to uniformly form an amorphous layer, and the magnetic permeability can be prevented from decreasing. On the other hand, by making the thickness of the soft magnetic metal ribbon 2 10 μm or more, it is possible to prevent voids or discontinuous parts from occurring on the surface of the soft magnetic metal ribbon 2, thereby suppressing a decrease in strength, and to prevent the soft magnetic metal ribbon 2 from easily breaking when wound into a roll, thereby preventing deterioration of workability. In addition, the soft magnetic metal ribbon 2 is less likely to deform when impregnated with the impregnating resin 3 and hardened after lamination, and the soft magnetic metal ribbon 2 is not distorted, thereby suppressing a decrease in magnetic permeability. For the same reason, the thickness of the soft magnetic metal ribbon 2 is more preferably 12 to 25 μm, and even more preferably 14 to 20 μm. The soft magnetic metal ribbon 2 is wound into a roll and used as a radially laminated annular magnetic body, or cut to a predetermined size and laminated to be used as a laminated magnetic body.

[0026] <<Impregnating resin>> By impregnating the resin 3 between the layers of the soft magnetic metal ribbon 2 of the heat-treated laminated core 1, the soft magnetic metal ribbon 2 can be fixed and the shape can be maintained. As the impregnating resin 3, an acrylic resin, an epoxy resin, a polyimide resin, a silicone resin, a silicone elastomer, or the like can be used. The glass transition temperature of the impregnating resin 3 used is preferably 85°C or higher. By setting the glass transition temperature to 85°C or higher, the dimensional change and the decrease in adhesive strength of the impregnating resin 3 due to aging in a high-temperature environment can be prevented, and the fixation of the soft magnetic metal ribbon 2 can be easily performed and the shape can be stably maintained. In addition, the soft magnetic metal ribbon 2 can be prevented from being distorted over time inside the soft magnetic metal ribbon 2, and the decrease in magnetic permeability can be suppressed. The glass transition temperature of the impregnating resin 3 is more preferably 125°C or higher, even more preferably 130°C or higher, and particularly preferably 150°C or higher. The impregnating resin 3 used is preferably an epoxy resin, which has a glass transition temperature that can be adjusted by changing the hardener, has a low viscosity before hardening, and has a high adhesive strength with the soft magnetic metal ribbon 2 after hardening.

[0027] The viscosity of the impregnating resin 3 when impregnating the gap between the layers of the soft magnetic metal ribbon 2 is preferably 2000 mPa·s or less. By impregnating the resin 3 at a relatively low viscosity as described above, it is possible to prevent the impregnating resin 3 from insufficiently penetrating the gap between the layers of the soft magnetic metal ribbon 2 and from excessively penetrating the gap by expanding and deforming the gap between the layers of the soft magnetic metal ribbon 2, thereby making it possible to set the ratio R4=S4 / S described below to 10.0% or less, and to suppress a decrease in magnetic permeability due to distortion of the soft magnetic metal ribbon 2. When using an impregnating resin 3 with a high viscosity, it is preferable to adjust the viscosity by adjusting the temperature or adding a diluent such as an organic solvent. It is more preferable that the viscosity of the impregnating resin 3 when impregnating the gap between the layers of the soft magnetic metal ribbon 2 is 550 mPa·s or less.

[0028] The impregnation with the impregnation resin 3 is preferably performed by immersing the uncured impregnation resin 3 at room temperature to 80° C. for 10 to 60 minutes under an impregnation pressure of normal pressure to reduced pressure (−0.05 MPaG). The temperature can be adjusted according to the viscosity of the impregnation resin 3 used. By setting the impregnation pressure to −0.05 MPaG or more, it is possible to suppress the occurrence of excessively permeated portions caused by the expansion and deformation of the interlayer space of the soft magnetic metal ribbon 2, and to make it possible to set the ratio R4=S4 / S described below to 10.0% or less, thereby suppressing the occurrence of distortion of the soft magnetic metal ribbon 2 and suppressing the decrease in magnetic permeability. It is more preferable that the impregnation pressure is normal pressure. In order to efficiently remove air bubbles generated between the layers of the soft magnetic metal ribbon 2 during immersion, the impregnation liquid can be swung, circulated, or vibrated. Furthermore, if it is difficult to impregnate the soft magnetic metal ribbon 2 (metal foil), it is preferable to apply an organic or inorganic adhesive to the surface before laminating the soft magnetic metal ribbon 2 (metal foil).

[0029] The laminated core 1 impregnated with the impregnating resin 3 is subjected to a heat treatment to harden the impregnating resin 3. The heat treatment temperature and time must be appropriate for the resin used, but for example, the heat treatment can be performed at a heat treatment temperature of 50 to 200°C for a heat treatment time of 0.5 to 10 hours. The heat treatment can also be performed stepwise in several steps starting from a low temperature.

[0030] Returning to the explanation of the laminated core 1, the laminated core 1 can be produced by bundling raw metal foils of a predetermined size and shape or winding them into a roll. The filling rate of the metal foil can be adjusted by the binding force when bundling the metal foils or the tension when winding them, and can be adjusted to, for example, a range of 65 vol% to 85 vol%. By setting the filling rate of the metal foil to, for example, 65 vol% or more, the ratio of the magnetic body is prevented from becoming too small, so that the magnetic permeability does not decrease, and the volume of the laminated core 1 can be reduced. On the other hand, by setting the filling rate of the metal foil to, for example, 85 vol% or less, the interlayer distance d of the soft magnetic metal ribbons 2 is prevented from becoming too small, and the impregnated resin 3 can be sufficiently permeated between the layers of the soft magnetic metal ribbons 2, making it easy to solidify and mold.

[0031] The laminated metal foil is heat-treated to remove distortion caused during molding. Furthermore, nanocrystals can be precipitated inside the amorphous alloy by heat-treating it. The heat treatment temperature can be, for example, 350°C to 700°C. The heat treatment is preferably performed in an inert atmosphere such as nitrogen or argon, or in the air.

[0032] In the example shown in FIG. 1, the laminated core 1 is an integral type, but in order to improve the ease of attachment to a cable, the laminated core 1 can be divided into at least two or more parts in the circumferential direction to form a split core. Alternatively, the laminated core 1 can be formed by combining, for example, a plurality of annular laminated magnetic pieces having discontinuous parts in the circumferential direction in the axial direction. In this case, it is preferable that the discontinuous parts adjacent in the axial direction do not overlap when viewed in the axial direction (particularly, that they do not have overlapping parts). In the case of a split core as described above, or a laminated core consisting of a combination of a plurality of annular laminated magnetic pieces having discontinuous parts, the performance is more stable if the contact surfaces between the magnetic pieces are less likely to deform due to changes over time. By using a resin with a high glass transition temperature to bond the soft magnetic metal ribbon 2, the shape of the contact surface is stable, especially in a usage environment exposed to high temperatures, and the surface roughness is less likely to deteriorate, so that stable performance can be maintained even at high temperatures.

[0033] As described above, the laminated core 1 of this embodiment is a laminated core made of a magnetic material formed by laminating the soft magnetic metal ribbons 2, and has the impregnated resin 3 impregnated between the layers of the soft magnetic metal ribbons 2. In the laminated core 1 of this embodiment, the total interlayer distance d of the soft magnetic metal ribbons 2 is S, and the average interlayer distance d of the soft magnetic metal ribbons 2 is d ave The average interlayer distance between the layers of the soft magnetic metal ribbon 2 is d ave When the total interlayer distance between layers that is four times or more is S4, the ratio R4=S4 / S of the total S to the total S is 10.0% or less. The effects of the laminated core 1 of this embodiment will be described below.

[0034] According to the laminated core 1 of the present embodiment, since the impregnated resin 3 is impregnated between the layers of the soft magnetic metal ribbon 2, the soft magnetic metal ribbon 2 can be fixed and the shape can be maintained. Since the ratio R4=S4 / S is 10.0% or less, the occurrence of distortion in the soft magnetic metal ribbon 2 can be suppressed, and the laminated core 1 can achieve high magnetic permeability. For the same reason, the ratio R4=S4 / S is preferably 5.0% or less.

[0035] Here, the glass transition temperature of the impregnating resin 3 between the layers of the soft magnetic metal ribbon 2 is preferably 85°C or higher. Recently, products using laminated cores have been widely used for electric vehicles, but the temperature environment in which they are used is becoming higher due to high-speed operation and high output. Therefore, the impregnating resin used to solidify and mold the laminated core is also required to have high heat resistance. The heat resistance can be improved by having the glass transition temperature, which is one of the indexes of heat resistance, in the above range. For the same reason, the glass transition temperature of the impregnating resin 3 between the layers of the soft magnetic metal ribbon 2 is more preferably 125°C or higher. It has been found that when a laminated core 1 is impregnated with an impregnating resin 3 having high heat resistance (for example, an impregnating resin 3 having a glass transition temperature of 85°C or higher), the viscosity tends to be high when the glass transition temperature is high, and this causes the spaces between the layers of the soft magnetic metal ribbon 2 to expand and deform, resulting in portions of excessive penetration, and also causes large thermal contraction during hardening, making the soft magnetic metal ribbon 2 particularly susceptible to distortion, resulting in a decrease in magnetic permeability. According to the laminated core 1 of the present disclosure, in consideration of heat resistance, even when the impregnating resin 3 having a high glass transition temperature as described above is used, by setting the ratio R4=S4 / S to 10.0% or less, it is possible to suppress the occurrence of distortion in the soft magnetic metal ribbon 2 and achieve high magnetic permeability for the laminated core 1, thereby achieving both heat resistance and high magnetic permeability.

[0036] In this embodiment, the impedance relative permeability μrz of the laminated core 1 at 100 kHz is preferably 10,000 or more. As will be shown in the examples described later, by setting the ratio R4=S4 / S to 10.0% or less, such a high impedance relative permeability μrz at 100 kHz can be achieved. In particular, even when an impregnating resin 3 with high heat resistance (e.g., an impregnating resin 3 with a glass transition temperature of 85° C. or more) is used, such a high impedance relative permeability μrz at 100 kHz can be achieved.

[0037] <Noise filter> The noise filter according to one embodiment of the present invention uses the laminated core 1 of the above embodiment. According to the noise filter using such a laminated core 1, a high noise suppression effect can be obtained because the laminated core 1 has high magnetic permeability. As a result, it can be used as a noise countermeasure core that is attached to the power cable of electronic devices such as automobiles, power generation / power supply facilities, communication devices, and OA / FA devices, and suppresses noise generated within these electronic devices or noise generated outside and propagating through the cable. In particular, when the glass transition temperature of the impregnated resin 3 of the laminated core 1 is high (preferably 85°C or higher), the heat resistance can also be improved, and it is possible to achieve both heat resistance and a high noise suppression effect. In the noise filter of the present disclosure, the ratio R4=S4 / S of the total S4 is preferably 10.0% or less, and the ratio R4 is preferably 5.0% or less. The glass transition temperature of the impregnating resin 3 between the layers of the soft magnetic metal ribbon 2 is preferably 85° C. or more, and more preferably 125° C. or more. The soft magnetic metal ribbon 2 is preferably made of a nanocrystalline alloy or an amorphous alloy. The impedance relative permeability μrz at 100 kHz of the laminated core 1 used in the noise filter of the present disclosure is preferably 10,000 or more.

[0038] <Magnetic core> A magnetic core according to one embodiment of the present invention uses the laminated core of the above embodiment. A magnetic core using such a laminated core 1 can obtain high efficiency because the laminated core 1 has high magnetic permeability. For example, by winding a conductor wire around the laminated core 1 as a primary winding, the laminated core 1 can be mounted on an electronic board and used as a common mode choke coil that suppresses noise. Furthermore, by winding a conductor wire around the laminated core 1 as a primary winding and a secondary winding, the laminated core 1 can also be used as a transformer for power conversion. In particular, when the glass transition temperature of the impregnated resin 3 of the laminated core 1 is high (preferably 85° C. or higher), the heat resistance can be improved, and both heat resistance and high efficiency can be achieved. In the magnetic core of the present disclosure, the ratio R4=S4 / S of the total S4 is preferably 10.0% or less, and the ratio R4 is preferably 5.0% or less. The glass transition temperature of the impregnating resin 3 between the layers of the soft magnetic metal ribbon 2 is preferably 85° C. or more, and more preferably 125° C. or more. The soft magnetic metal ribbon 2 is preferably made of a nanocrystalline alloy or an amorphous alloy. The impedance relative permeability μrz at 100 kHz of the laminated core 1 used in the magnetic core of the present disclosure is preferably 10,000 or more. EXAMPLES

[0039] Examples of the present invention will be described below, but the present invention is not limited to these.

[0040] (Examples 1 and 2) A laminated core was produced by laminating soft magnetic metal ribbons. First, an alloy melt containing, in atomic %, Cu: 1%, Nb: 3%, Si: 13.5%, B: 9%, and the remainder essentially consisting of Fe was quenched by a single roll method to obtain a ribbon-shaped Fe-based amorphous alloy having a width of 10 mm and a thickness of 15 μm. The Fe-based amorphous alloy was wound to form a cylindrical shape having an outer diameter of 28.5 mm, an inner diameter of 18.0 mm, and a height of 10 mm. The cylindrical Fe-based amorphous alloy was inserted into a heat treatment furnace kept at 490 ° C. under an argon atmosphere and subjected to heat treatment for 10 minutes. Then, an annular magnetic body made of an Fe-based nanocrystalline alloy was produced. The obtained annular magnetic body was immersed in a solution prepared by mixing an epoxy resin and a curing agent in a specified ratio and kept at 50 ° C. for 20 minutes under normal pressure to impregnate the annular magnetic body with the resin. Thereafter, the annular magnetic bodies were held in air at 180° C. (in the case of Example 1) or 160° C. (in the case of Example 2) for 8 hours to harden the resin, thereby obtaining a laminated core.

[0041] A Keysight 4294A impedance analyzer was used to measure the impedance relative permeability of the obtained laminated core at a frequency of 100 kHz. Using a fixture for lead wire measurement (16047E), a Tanaka Electric Wire H-PCV, Φ0.5 mm single-wire lead wire was passed through the laminated core for one turn to measure the impedance Z. The impedance Z was converted to the impedance relative permeability μrz by μrz=Z×Lm / (2πμ0f×Ae). Here, μ0 is the vacuum permeability, Lm is the average magnetic path length, f is the measurement frequency, and Ae is the effective cross-sectional area. When the outer diameter of the laminated core is OD, the inner diameter is ID, and the height is HT, the calculation is as follows: Lm=π(OD+ID) / 2, Ae=(OD-ID)×HT / 2×dr. dr is the filling rate of the magnetic material, which was 0.75 in this case.

[0042] The coercive force was measured using an automatic measuring coercive force meter K-HC1000 manufactured by Tokyo Tokushu Kogyo Co., Ltd. The measurement mode was SLOW, the measurement direction was the radial direction of the laminated core, and the average value was obtained by measuring three times at equal intervals of 120° in the circumferential direction. The viscosity of the impregnated resin was measured using a Brookfield viscometer DV1M manufactured by Eiko Seiki Co., Ltd. The resin was heated to a specified temperature in advance, and the motor rotation speed was adjusted so that the spindle torque was within 10 to 90%. The glass transition temperature of the impregnated resin was measured using a differential scanning calorimeter DSC3500 manufactured by NETZSCH. A small piece of 4 mm x 4 mm x 1 mm was cut out from the laminated core that had been impregnated with the resin and cured, placed in a Pt container, and heated at a heating rate of 10 °C to 570 °C with Ar gas flowing at 20 mL / min, and the glass transition temperature was obtained from the start of the endothermic reaction. The glass transition temperature of the impregnated resin of the laminated core produced was 150 °C.

[0043] The interlayer distance of the soft magnetic metal ribbon of the laminated core was measured on the side of the laminated core shown in Figure 2. The side was finished with abrasive paper of #500 to #2000, and the interlayer distance of the soft magnetic metal ribbon was measured from an image observed at 500x objective magnification using a Rirox digital microscope RH-2000. Observation was performed in one straight line in the thickness direction of the soft magnetic metal ribbon from the inner circumference side to the outer circumference side of the laminated core, covering 90% of the thickness w of the laminated core (45% radially inward and 45% radially outward from the radial center position). The observation locations were three straight lines (three radial lines) equally spaced at 120° in the circumferential direction as shown in Figure 3, and the average interlayer distance d of the soft magnetic metal ribbon was measured. ave Based on the obtained interlayer distance of the soft magnetic metal ribbon, the average interlayer distance d of the soft magnetic metal ribbon with respect to the total interlayer distance S of the soft magnetic metal ribbon was calculated. ave More than four times (4d ave The ratio S4 / S×100(%) of the total interlayer distance S4 of the soft magnetic metal ribbons (above) was calculated.

[0044] The manufacturing conditions and measurement results of the obtained laminated core are shown in the following Table 1. In addition, Fig. 4 shows one of the observation images obtained by measuring the interlayer distance of the metal ribbon in Example 1, and Fig. 5 shows a histogram of the interlayer distance of the metal ribbon in Example 1.

[0045] Example 3 After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by mixing the base resin and the curing agent of epoxy resins having different glass transition temperatures in a specified ratio, and the annular magnetic body was immersed in the solution kept at 50°C under normal pressure for 20 minutes to impregnate the annular magnetic body with the resin. The resin was then cured by holding it in air at 150°C for 5 hours to obtain a laminated core. The measurement method was the same as in Example 1. The glass transition temperature of the impregnated resin of the prepared laminated core was 125°C. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0046] Example 4 After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by adding 0.5 wt% of a curing accelerator to a solution in which epoxy resins with different glass transition temperatures and a curing agent were mixed in a specified ratio, and the annular magnetic body was immersed in the solution maintained at 25°C under normal pressure for 1 hour to impregnate the annular magnetic body with the resin. The resin was then cured by holding it in the air at 80°C for 3 hours to obtain a laminated core. The measurement method was the same as in Example 1. The glass transition temperature of the impregnated resin of the prepared laminated core was 85°C. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0047] (Examples 5 and 6) After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by mixing epoxy resin and hardener in a specified ratio, and the annular magnetic body was immersed in the solution, which was kept at 30°C. The solution was evacuated to -0.05 MPaG and held for 10 minutes, and then the pressure was released to atmospheric pressure to impregnate the annular magnetic body with the resin. The resin was then hardened by holding it in the air at 180°C (in the case of Example 5) and 160°C (in the case of Example 6) for 8 hours, to obtain a laminated core. The measurement method was the same as in Example 1. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0048] (Examples 7 and 8) After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by adding 1 wt% of a curing accelerator to a solution in which an epoxy resin and a curing agent were mixed in a specified ratio, and the annular magnetic body was immersed in the solution kept at 50°C under normal pressure for 20 minutes to impregnate the annular magnetic body with the resin. The resin was then cured by holding in the air at 180°C (in the case of Example 7) and 160°C (in the case of Example 8) for 8 hours to obtain a laminated core. The measurement method was the same as in Example 1. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0049] Example 9 After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by adding 1 wt% of a curing accelerator to a solution in which an epoxy resin and a curing agent were mixed in a specified ratio, and the annular magnetic body was immersed in the solution, which was kept at 50°C, and the solution was evacuated to -0.05 MPaG and held for 10 minutes, after which the pressure was released to atmospheric pressure and the annular magnetic body was impregnated with the resin. The resin was then cured by holding it in the air at 180°C for 8 hours to obtain a laminated core. The measurement method was the same as in Example 1. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0050] (Examples 10 and 11) After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by adding 1 wt% of a curing accelerator to a solution in which an epoxy resin and a curing agent were mixed in a specified ratio, and the annular magnetic body was immersed in the solution maintained at 25°C under normal pressure for 1 hour to impregnate the annular magnetic body with the resin. The resin was then cured by holding in the air at 180°C (in the case of Example 10) and 160°C (in the case of Example 11) for 8 hours to obtain a laminated core. The measurement method was the same as in Example 1. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0051] Example 12 After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by mixing epoxy resins and curing agents with different glass transition temperatures in a specified ratio, and the annular magnetic body was immersed in the solution, which was kept at 50°C. The solution was evacuated to -0.05 MPaG and held for 10 minutes, and then the pressure was released to atmospheric pressure to impregnate the annular magnetic body with the resin. The resin was then hardened by holding it in the air at 80°C for 3 hours to obtain a laminated core. The measurement method was the same as in Example 1. The glass transition temperature of the impregnated resin of the prepared laminated core was 50°C. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0052] Example 13 After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by mixing the same epoxy resin and curing agent as in Example 12 in a specified ratio, and the annular magnetic body was immersed in the solution kept at 80°C. The solution was evacuated to -0.05 MPaG and held for 10 minutes, and then the pressure was released to atmospheric pressure to impregnate the annular magnetic body with the resin. The resin was then hardened by holding it in the air at 80°C for 3 hours to obtain a laminated core. The measurement method was the same as in Example 1. The glass transition temperature of the impregnated resin of the prepared laminated core was 50°C. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0053] (Comparative Examples 1 and 2) After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by mixing epoxy resin and hardener in a specified ratio, and the annular magnetic body was immersed in the solution maintained at 25°C. The solution was evacuated to -0.10 MPaG and held for 10 minutes, and then the pressure was released to atmospheric pressure to impregnate the annular magnetic body with the resin. The resin was then hardened by holding in the atmosphere at 180°C (in the case of Comparative Example 1) and 160°C (in the case of Comparative Example 2) for 8 hours to obtain a laminated core. The measurement method was the same as in Example 1. Table 1 shows the preparation conditions and measurement results of the obtained laminated core. FIG. 6 shows one of the observation images obtained by measuring the metal strip interlayer distance in Comparative Example 1, and FIG. 7 shows a histogram of the metal strip interlayer distance in Comparative Example 1.

[0054] Comparative Example 3 After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by mixing epoxy resin and hardener in a specified ratio, and the annular magnetic body was immersed in the solution, which was kept at 30°C. The solution was evacuated to -0.10 MPaG and held for 10 minutes, and then the pressure was released to atmospheric pressure to impregnate the annular magnetic body with the resin. The resin was then hardened by holding it in the air at 180°C for 8 hours to obtain a laminated core. The measurement method was the same as in Example 1. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0055] (Comparative Examples 4 and 5) After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by adding 1 wt% of a curing accelerator to a solution in which an epoxy resin and a curing agent were mixed in a specified ratio, and the annular magnetic body was immersed in the solution maintained at 25°C, and after evacuating to -0.1 MPaG and holding for 10 minutes, the pressure was released to atmospheric pressure to impregnate the annular magnetic body with the resin. The resin was then cured by holding for 8 hours in the atmosphere at 180°C (in the case of Comparative Example 4) and 160°C (in the case of Comparative Example 5), to obtain a laminated core. The measurement method was the same as in Example 1. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0056] Comparative Example 6 After preparing the annular magnetic body in the same manner as in Example 1, a solution was prepared by adding 1 wt% of a curing accelerator to a solution in which an epoxy resin and a curing agent were mixed in a specified ratio, and the annular magnetic body was immersed in the solution, which was kept at 50°C, and the solution was evacuated to -0.1 MPaG and held for 10 minutes, after which the pressure was released to atmospheric pressure and the annular magnetic body was impregnated with the resin. The resin was then cured by holding it in the air at 180°C for 8 hours to obtain a laminated core. The measurement method was the same as in Example 1. Table 1 shows the preparation conditions and measurement results of the obtained laminated core.

[0057] [Table 1]

[0058] In the observation image of the soft magnetic metal ribbon of Example 1 shown in FIG. 4, in which the interlayer distance is measured, the metal ribbon interval (interlayer distance) is uniform, whereas in the observation image of Comparative Example 1 shown in FIG. 6, there are areas where the spacing between the layers of the soft magnetic metal ribbon is wide, causing distortion in the metal ribbon. In the histogram of the interlayer distance of the soft magnetic metal ribbon of Comparative Example 1 shown in FIG. 7, there are many areas where the interlayer distance of the soft magnetic metal ribbon is wide. As shown in Table 1, the average d of the interlayer distance d of the soft magnetic metal ribbon with respect to the total S of the interlayer distances d of the soft magnetic metal ribbon of Example 1 is ave The ratio R4=S4 / S of the total interlayer distance S4 of the soft magnetic metal ribbons that is four or more times larger than the above is 2.2%, whereas the ratio R4=S4 / S of Comparative Example 1 is as large as 15.2%. The impedance relative permeability μrz of Example 1 is 12,270, whereas the impedance relative permeability μrz of Comparative Example 1 is as low as 8048, and it is found that the smaller the ratio R4=S4 / S, the higher the μrz.

[0059] Looking at other examples and comparative examples, it can be seen that even when an impregnated resin with a high glass transition temperature is used, a laminated core with μrz exceeding 10,000 can be obtained by setting R4 to 10% or less. When comparing the ratio R3 (=S3 / S×100)%, which is the ratio of the total metal strip interlayer distance S3 that is three times or more the average interlayer distance of the soft magnetic metal strip 2 to the total interlayer distance d of the soft magnetic metal strip, in a laminated core such as Example 1 with μrz exceeding 10,000, R3 is 10.4%, which is equivalent to R3=10.3% of a laminated core such as Comparative Example 6 with μrz of 10,000 or less, and no significant difference is observed. Therefore, a laminated core with R4 of 10% or less can be used stably in a high-temperature environment while having high magnetic permeability, and can be expected to have a high noise suppression effect in a noise filter, and can be expected to reduce losses in the magnetic core of a transformer or motor. [Industrial Applicability]

[0060] The laminated core of the present disclosure can be attached to the power cables of electronic devices such as automobiles, power generation / power supply facilities, communication devices, and OA / FA devices, and can be used as a noise suppression core that suppresses noise generated within these electronic devices or that generated externally and propagates through the cables. In addition, by winding a conductor wire around the laminated core of the present disclosure as a primary winding, it can be mounted on an electronic board and used as a common mode choke coil that suppresses noise. Furthermore, by winding a conductor wire around the laminated core of the present disclosure as a primary winding and secondary winding, it can also be used as a transformer for power conversion. [Explanation of symbols]

[0061] 1: Laminated core, 2: Soft magnetic metal ribbon, 3: Resin (impregnated resin)

Claims

1. A laminated core made of a magnetic material formed by laminating soft magnetic metal ribbons, A resin is disposed between the layers of the soft magnetic metal ribbon, The total interlayer distance d of the soft magnetic metal ribbons is S, and the average interlayer distance d of the soft magnetic metal ribbons is d ave and the interlayer distance between the layers of the soft magnetic metal ribbon is the average d ave The sum of the interlayer distances between layers that are four times or more is S 4 When The sum S for the sum S 4 Ratio of R 4 = S 4 / S is 0.8% or more and 10.0% or less, A laminated core comprising an annular magnetic body.

2. 2. The laminated core according to claim 1, wherein the glass transition temperature of the resin between the layers of the soft magnetic metal ribbon is 85° C. or higher.

3. 2. The laminated core according to claim 1, wherein the glass transition temperature of the resin between the layers of the soft magnetic metal ribbon is 125° C. or higher.

4. The ratio R 4 = S 4 4. The laminated core according to claim 1, wherein / S is 5.0% or less.

5. The laminated core according to any one of claims 1 to 3, wherein the soft magnetic metal ribbons are made of a nanocrystalline alloy.

6. The laminated core according to any one of claims 1 to 3, wherein the soft magnetic metal ribbons are made of an amorphous alloy.

7. The laminated core according to any one of claims 1 to 3, wherein the impedance relative permeability μrz at 100 kHz is 10,000 or more.

8. 4. The laminated core according to claim 1, which is formed by combining a plurality of annular laminated magnetic pieces having discontinuous portions that are interrupted in the circumferential direction.

9. A noise filter using the laminated core according to any one of claims 1 to 3.

10. A magnetic core for a transformer or a motor, comprising the laminated core according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Choke coil magnetic core and manufacture thereof

    JP1997027413A

  • Method of manufacturing small-loss gapped core

    JP2001319820A

  • Magnetic substrate

    JP2002151316A

  • Laminated magnetic core and magnetic component

    JP2004356468A

  • Laminate, and antenna

    JP2009194724A